Innovation in Cultural Governance to Enhance Regional Identity and Foster Competitiveness in Bone Regency - Feby Triadi; Nur Faidzaturrahmah; M Awaluddin A; Erviandy Erviandy; Novi Novi (Public Resource Innovation Management and Excellence, 2025)
The dynamics of globalization, modernization, and shifting values of the younger generation demand innovation in cultural governance to remain relevant and competitive. This study aims to analyze the forms of cultural governance innovation implemented by the Bone Regency Government and their impact on strengthening cultural identity and increasing regional competitiveness. The research method used is a qualitative approach with data collection techniques through in-depth interviews, participatory observation, and analysis of policy documents. The results show that cultural governance innovation in Bone includes the integration of digital technology in cultural promotion, multi-stakeholder collaboration between the government, indigenous communities, and business actors, and the revitalization of cultural activities based on community participation. These innovations not only strengthen the image and identity of Bugis culture at the local and national levels but also open up creative economic opportunities that contribute to increasing regional competitiveness. This study recommends strengthening regulations, program sustainability, and increasing the capacity of cultural actors as long-term strategies for cultural governance in Bone Regency.